Depressive and anxious symptoms and the risk of secondary school non-completion. (September 2017) - Brière, Frédéric N.; Pascal, Sophie; Dupéré, Véronique; Castellanos-Ryan, Natalie; Allard, Francis; Yale-Soulière, Gabrielle; Janosz, Michel
Abstract : Background: Evidence regarding the association between adolescent internalising symptoms and school non-completion has been limited and inconclusive. Aims: To examine whether depressive and anxious symptoms at secondary school entry predict school non-completion beyond confounders and whether associations differ by baseline academic functioning. Method: We used logistic regression to examine associations between depressive and anxious symptoms in grade 7 (age 12–14) and school non-completion (age 18–20) in 4962 adolescents. Results: Depressive symptoms did not predict school non-completion after adjustment, but moderation analyses revealed an association in students with elevated academic functioning. A curvilinear association was found for anxiety: both low and high anxious symptoms predicted school non-completion, although only low anxiety remained predictive after adjustment. Conclusions: Associations between internalising symptoms and school non-completion are modest. Common school-based interventions targeting internalising symptoms are unlikely to have a major impact on school non-completion, but may prevent non-completion in selected students.